Dom rodzinny jako miejsce mitobiograficzne Zbigniewa Żakiewicza - Olga Pańkowa (Zagadnienia Rodzajów Literackich)
On the basis of literary sketches from the Frozen in Time volume and Zbigniew Żakiewicz’s novels Lupine Meadows, The Abacz Clan and Wilio, in the Depths of the Sea, a symbolic connection between the writer’s family home and the past, especially his childhood, is presented. In the article, the house is regarded as a pictorial embodiment of lost homeland and the destruction of the protagonist/narrator’s private world following his exile from the Borderlands. The space of the family home collapses, and thus ceases to evoke a feeling of belonging, to be a sign of childhood order. In Żakiewicz’s works, memory as an identity category is depicted in material, social, symbolic and personalistic dimensions. Family home is related to the material side of things, as well as behaviors, relations, ideas, and values. It becomes a specific marker which, depending on context, can be used in a variety of ways, acting as a metonymy or synecdoche. Space as a component of identity extends from autobiographical to collective memory, it is the knowledge about the roots from which one grows. The change of individual and collective space-time leads the writer to identify what is “home” and what is “memory”: “home” becomes a model of “memory,” and “memory” a model of a “home” that exists thanks to memories and dreams. Zbigniew Żakiewicz shows how space shrinks, how his family home turns into a house of cards within a few years and, dependent on the individual perspective, loses its entire spiritual and material treasure for the family.